Quasi-Threshold Effect for Energy Dependence of Resonant Transition X-Ray Radiation of 300-700 MeV Electrons Generated in Be Layered Target - Andreyashkin M. Yu.; Kaplin V. V. Valeriy Viktorovich; Zabaev V. N. Viktor Nikolaevich; Uglov S. R. Sergey Romanovich; Endo I.; Kobayashi T. (1993, 1993)
В фонде НТБ ТПУ отсутствует